What the new institutional economics owes Marx - De Dios, Emmanuel S. (2019)
The bicentennial of Marx’s birth (2018) and the earlier sesquicentennial of Capital’s publication (2017) are opportunities to examine aspects of new institutional economics and incentive theory with an affinity to or origin in concepts first put forward by Marx. A major idea pertains to industrial organization and the theory of the firm. We compare Marxian and new-institutional insights and conversely attempt to interpret some of Marx’s ideas from a new-institutional viewpoint.
Keywords: Marx, Karl, 1818-1883; Marxian economics; Institutional economics